2013
DOI: 10.1128/jvi.01539-13
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Dendritic Cells Isolated from Healthy Seropositive Donors Are Sites of Human Cytomegalovirus Reactivation In Vivo

Abstract: Primary infection with human cytomegalovirus (HCMV) is generally asymptomatic in healthy individuals and results in a lifelong infection of the host. In contrast, in immunosuppressed transplant recipients and late-stage AIDS patients, HCMV infection and reactivation can result in severe disease or death. In vivo, latency is established in bone marrow CD34؉ progenitor cells with reactivation linked with their differentiation to macrophages and dendritic cells (DCs). However, previous analyses have relied on ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 54 publications
4
59
0
Order By: Relevance
“…4 At the same time, monocytes are known to be sites of CMV latency, 48 although they are not permissive for virus replication. In the absence of HIV-1, induction of replicating CMV has been shown to occur with the terminal differentiation of monocytes to myeloid dendritic cells, 49 and in vitro studies have demonstrated that monocyte to macrophage differentiation leads to production of infectious virus. [50][51][52] If HIV-1 infection activates monocytes and macrophages, 53 it is likely that CMV could be reactivated and replicate leading to an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…4 At the same time, monocytes are known to be sites of CMV latency, 48 although they are not permissive for virus replication. In the absence of HIV-1, induction of replicating CMV has been shown to occur with the terminal differentiation of monocytes to myeloid dendritic cells, 49 and in vitro studies have demonstrated that monocyte to macrophage differentiation leads to production of infectious virus. [50][51][52] If HIV-1 infection activates monocytes and macrophages, 53 it is likely that CMV could be reactivated and replicate leading to an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…CMV prophylaxis with 100 days of valganciclovir was given to the D+RÀ serostatus group only, with dose adjustment for renal function. Serial whole blood samples were taken for CMV DNA polymerase chain reaction in all patients at day 0 (before transplantation) and then at weeks 1,2,3,4,6,8,10,12,16,20,24,28,34,40,46, and 52. The clinical team remained unaware of these results, and no changes in clinical management ensued (it is not unit policy to undertake viral load testing and preemptive therapy in the context of asymptomatic CMV infection, as is the case in most centers, so these assessments were undertaken for research purposes only).…”
Section: Assessment Of CMV Serostatus Infection and Diseasementioning
confidence: 99%
“…It is well established that HCMV can infect and induce latency in pluripotent mononuclear cells in the bone marrow, particularly CD34 + . Even though monocytes carry the viral genome, replicating virus can only be detected upon cell differentiation (Goodrum et al, 2002;Hahn et al, 1998;Reeves & Sinclair, 2013). The inability of MCMV to produce progeny in the undifferentiated cells of the bone marrow does not exclude the possibility of initial stages of replication occurring, during the acute phase of infection, before latency be established.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that MCMV can infect different cell types; however, it exhibits selectivity for specific cells at early points of infection (Hsu et al, 2009). Viral dissemination is mainly associated with cells from the myeloid lineage (Bale & O'Neil, 1989;Hanson et al, 1999;Noda et al, 2006;Stoddart et al, 1994), and mononuclear phagocytes (monocytes, macrophages and dendritic cells), the very first cellular defence against infection at entry sites, are recognized reservoirs of MCMV Hamano et al, 1998;Reeves & Sinclair, 2013;Stoddart et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation